2016
DOI: 10.11622/smedj.2016089
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and antihypertensive medication profile in a multiethnic Asian population of stable chronic kidney disease patients

Abstract: RESULTS 613 patients (55.1% male; 74.7% Chinese, 6.4% Indian, 11.4% Malay; 35.7% diabetes mellitus) with a mean age of 57.8 ± 14.5 years were recruited. Mean SBP was 139 ± 20 mmHg, DBP was 74 ± 11 mmHg, serum creatinine was 166 ± 115 µmol/L and GFR was 53 ± 32 mL/min/1.73 m 2 . At a lower GFR, SBP increased (p < 0.001), whereas DBP decreased (p = 0.0052). Mean SBP increased in tandem with the number of antihypertensive agents used (p < 0.001), while mean DBP decreased when ≥ 3 antihypertensive agents were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Similarly, the rate was 77.5% in the UK study . Additionally, in a study performed in Singapore, the utilization of RASIs was >70.0% in patients with CKD stages 3‐4 . Therefore, the decreased utilization of RASIs in patients with CKD stages 3 and 4 might contribute to the reduced control of hypertension among these patients in the present study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similarly, the rate was 77.5% in the UK study . Additionally, in a study performed in Singapore, the utilization of RASIs was >70.0% in patients with CKD stages 3‐4 . Therefore, the decreased utilization of RASIs in patients with CKD stages 3 and 4 might contribute to the reduced control of hypertension among these patients in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, diuretics should be a rational choice for antihypertensive treatment for CKD patients. This was found to be the case in the CRIC study with 84%, 62.6% in the GCKD study, 65.7% in the MERENA study, and 43.8% in the Singapore study . In addition, most CKD patients displayed salt sensitive features in their hypertension, indicating that increased salt intake could aggravate fluid retention and BP elevation.…”
Section: Discussionmentioning
confidence: 79%
“…It has been recognized that target SBPs are harder to attain in older participants in whom widening of pulse pressure may occur when diastolic blood pressure levels are lowered in the course of treatment. [34] Since patients with CKD tend to be older and have more cardiovascular risk factors, it is advisable to individualize treatment in patients according to their age and comorbidities.…”
Section: Management Of Hypertension In Ckd General Rulesmentioning
confidence: 99%
“…The KDIGO 2012 guidelines recommend a target blood pressure of <130/80 mmHg for patients with albuminuria. [34] In post hoc and subgroup analyses of the modification of diet in renal disease (MDRD) and The African-American Study of Kidney Disease and Hypertension (AASK) studies, a target MAP of 92 mmHg was associated with a slower decline in kidney function in patients with proteinuria of >0.3-1 g/day. [35,36] The Steno-2 study showed a reduced risk of cardiovascular disease with a blood pressure target of 130/80 mmHg compared to 135/85 mmHg in patients with Type 2 diabetes and microalbuminuria.…”
Section: Ckd With Proteinuriamentioning
confidence: 99%
“…[3] Besides diagnosis, even with good follow-up and access to medical care, hypertension may not be adequately controlled with current clinical practice and therapeutic drugs. [4] Perhaps, newer technologies such as retinal photography with computerized evaluation, it is possible to quantitatively assess the changes of blood vessels in hypertensive patients, particularly the adequacy of therapy. [5] Without higher fidelity assessment and follow-up, the residual risks of treated hypertension on mortality and complications cannot be completely eliminated.…”
mentioning
confidence: 99%